The Results of 16 Years of Iodization: Assessment of Iodine Deficiency Among School-age Children in Antalya, Turkey - Gamze Çelmeli; Yusuf Çürek; İkbal Özen Kücükçetin; Zümrüt Arslan Gülten; Sebahat Özdem; Sema Akçurin; İffet Bircan (Galenos Yayincilik, 2020)
Objective:Iodine deficiency (ID) continues to be a problem around the world. This study investigated the prevalence of ID and goiter among school-age children in the city center of Antalya, Turkey. The aim was to investigate the effect of an iodization program, which had been running for sixteen years, on nutritional iodine status in this population.Methods:A total of 1,594 school children, aged 6-14 years, were included in this cross-sectional study. ID was evaluated based on median [interquartile range (IQR)] urine iodine/creatine (UI/Cr) (μg/g) ratio and median (IQR) UI concentrations (UIC) (μg/L). UICs were measured using the Sandell-Kolthoff method. Goiter was determined by palpation and staged according to World Health Organization classification.Results:Median (IQR) UIC was found to be 174.69 (119.17-242.83) μg/L, and UIC was found to be lower than 50 μg/L in 6.5% of the population. The median UI/Cr ratio increased from 62.3 to 163.3 μg/g and goiter rates had decreased from 34% to 0.3% over the 16 years of the program. However, 19% were still classified as ID (mild, moderate or severe) and, furthermore, 11.5% were classified as excessive iodine intake.Conclusion:Comparison of two cross-sectional studies, carried out 16-years apart, showed that Antalya is no longer an ID region. However, surveillance should be continued and the percentage of ID and iodine excess individuals in the population should be monitored to avoid emerging problems.